1984
DOI: 10.1111/1523-1747.ep12259203
|View full text |Cite
|
Sign up to set email alerts
|

Changes with Age in the Moisture Content of Human Skin

Abstract: A technique to measure the dynamic mechanical properties of human skin in vivo is described. The technique measures the propagation and attenuation of shear waves in skin tissue over a range of frequencies (8-1016 Hz). Results show that both the propagation velocity and attenuation of shear waves in skin are highly dependent upon the water content of the stratum corneum. The technique was used to measure the dynamic mechanical properties of the skin on the back of the left hand for a group of 16 men ranging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(46 citation statements)
references
References 9 publications
3
36
1
Order By: Relevance
“…The r 2 values obtained by linear regression analysis performed with the male and female data grouped together, show that on both the ® nger pad and the cheek, a substantial portion of the variation in hydration can be accounted for by age (p , 0.001). This result is consistent with that of Potts et al, (1984), who showed decreased water content in stratum corneum of the dorsum of male hands with age. On the web and the arm, however, the variation in hydration cannot be accounted for by age.…”
Section: Temperaturesupporting
confidence: 92%
“…The r 2 values obtained by linear regression analysis performed with the male and female data grouped together, show that on both the ® nger pad and the cheek, a substantial portion of the variation in hydration can be accounted for by age (p , 0.001). This result is consistent with that of Potts et al, (1984), who showed decreased water content in stratum corneum of the dorsum of male hands with age. On the web and the arm, however, the variation in hydration cannot be accounted for by age.…”
Section: Temperaturesupporting
confidence: 92%
“…Similar data have been reported by other investigators. 24) Differential scanning calorimetric studies suggested that the cutaneous water promotes the fluidity of the lipid bilayer and extends the lipid domain among the lipid polar groups. 25) As the stratum In panel (a), R S1 is the resistance of the stratum corneum, C S is the capacitance of the stratum corneum, and R S2 is the resistance of the viable epidermis and dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Such a selection was made in order to avoid interidividual variability as much as possible [6, 8, 10, 12]. Shear wave propagation is assumed to be influenced by the intrinsic skin tensile strength related to the density, elasticity and viscosity of the tissues [12].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a prototype device measuring the speed of propagation of an acoustic wave at the skin surface [6]. The shear wave propagation is inversely proportional to the stiffness and density of the tissues [6, 7, 8, 9, 10, 11, 12, 13]. It should be theoretically influenced by the preferential orientation of the dermal fibre networks and therefore indicate the direction of tension lines.…”
Section: Introductionmentioning
confidence: 99%